The Effectiveness of 1000 HPK E-Booklet Media on Improving Knowledge and Attitudes of Pregnant Women in Stunting Prevention - Pertiwi, Mumpuni Intan; Risnawati, Hani; Olivia, Maya; Keriswanies, Sekar (Universitas Muhammadiyah Sidoarjo, 2026)
Stunting is a condition of failing to grow in children due to chronic malnutrition from the beginning of life, and remains a major global nutrition problem. Pregnant women and their families as a prevention effort from the prenatal period (1000 HPK starts from pregnancy). E-booklet media is used because it makes it easier for the target to understand the information conveyed than verbal delivery alone; with the e-booklet, the target can directly observe the images and the explanations that accompany them. This study used a quasi-experimental design with a pre-test and post-test in a single group. Pregnant women, sample selection technique: purposive sampling (selected based on inclusion criteria and readiness to participate in interventions). E-booklet themed 1000 First Days of Life that focuses on stunting prevention through pregnant women's nutrition, care behaviors, immunizations, and infant feeding practices. Based on the analysis, respondents were included in the 21-35 years age category. The Wilcoxon Signed Rank Test is used to compare the knowledge of pregnant women before (pre-test) and after (post-test) the intervention. Asymp value. The sig. (2-tailed) Knowledge is 0.009, and the 0.011 attitude is smaller than the p< value of 0.05. There was a significant increase in pregnant women's knowledge and attitudes after counseling using an e-booklet, with average rankings of 0.009 and 0.011, respectively.